Cubic boron nitride sintered body and cutting tool

By introducing an intervening phase of aluminum, nitrogen, and oxygen between cBN particles and the binder phase, the tool life and resistance of cBN tools are enhanced, addressing the instability and wear issues in cutting high-strength hardened steels.

JP7614070B2Active Publication Date: 2025-01-15SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021174399
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-18
Filing Date
2021-10-26
Publication Date
2025-01-15
Estimated Expiration
2040-07-17

AI Technical Summary

Technical Problem

Cubic boron nitride (cBN) tools used for cutting hardened steel, particularly high-strength hardened steels, suffer from unstable tool life due to rapid wear and chipping caused by the detachment of cBN particles, leading to increased cutting resistance and defects.

Method used

Incorporating an intervening phase composed of aluminum, nitrogen, and oxygen between cBN particles and a binder phase, with specific atomic concentration ratios and thickness, to enhance stress absorption and adhesion, thereby improving fracture resistance and wear resistance.

Benefits of technology

The intervention phase effectively suppresses crack propagation and enhances the adhesion between cBN particles and the binder phase, resulting in improved tool life and reduced wear, allowing for higher cutting speeds without premature tool failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007614070000002
    Figure 0007614070000002
  • Figure 0007614070000003
    Figure 0007614070000003
  • Figure 0007614070000004
    Figure 0007614070000004
Patent Text Reader

Abstract

To improve the life of cBN tools. [Solution] The cubic boron nitride sintered body includes cubic boron nitride particles, a binder phase, and an intervening phase. The intervening phase is interposed between the cubic boron nitride particles and the binder phase. The intervening phase includes aluminum, nitrogen, boron, and oxygen. The sum of the average atomic concentration of aluminum contained in the intervening phase and the average atomic concentration of nitrogen contained in the intervening phase is 50.0 atomic % or more. The ratio of the average atomic concentration of nitrogen contained in the intervening phase to the average atomic concentration of boron contained in the intervening phase exceeds 1.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a cubic boron nitride sintered body and a cutting tool. This application claims priority to Japanese Patent Application No. 2019-133023, filed on July 18, 2019. The entire contents of the Japanese Patent Application are incorporated herein by reference. [Background technology]

[0002] Japanese Patent Laid-Open Publication No. 2015-044259 (Patent Document 1) discloses a cubic boron nitride sintered body. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-044259 A Summary of the Invention

[0004] The cubic boron nitride sintered body of the present disclosure comprises cubic boron nitride particles, a binder phase and an intervening phase. Cubic boron nitride particles account for 20% to 80% by volume of the cubic boron nitride sintered body. The total volume ratio of the binder phase and the intervening phase is calculated by subtracting the volume ratio of the cubic boron nitride particles from the volume ratio of the cubic boron nitride sintered body, which is 100% by volume. The binder phase comprises one or more components selected from the group consisting of compounds and solid solutions. Each of the compound and the solid solution includes a first element and a second element. The first element is at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen. The second element is at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, and aluminum in the periodic table. The intervening phase is interposed between the cubic boron nitride particles and the binder phase. The intervening phase contains aluminum, nitrogen, boron, and oxygen. The sum of the average atomic concentration of aluminum contained in the intervening phase and the average atomic concentration of nitrogen contained in the intervening phase is 50.0 atomic % or more. The ratio of the average atomic concentration of nitrogen contained in the intervening phase to the average atomic concentration of boron contained in the intervening phase exceeds 1.00. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is an example of a cross-sectional image of a cBN sintered body according to this embodiment. [Diagram 2] FIG. 2 shows the mapping result of Al in the image of FIG. [Diagram 3] FIG. 3 is a graph showing the results of the line analysis. [Figure 4] FIG. 4 is a graph showing the atomic concentration distribution of Al in FIG. [Diagram 5] FIG. 5 is a graph showing the atomic concentration distribution of N in FIG. [Figure 6] FIG. 6 is a graph showing the atomic concentration distribution of B in FIG. [Figure 7] FIG. 7 is a graph showing the atomic concentration distribution of O in FIG. [Figure 8] FIG. 8 is a graph showing the atomic concentration distribution of C in FIG. [Figure 9] FIG. 9 is a flowchart showing a method for producing a cBN sintered body in this embodiment. [Figure 10] FIG. 10 is an example of a backscattered electron image of a cBN sintered body. [Figure 11] FIG. 11 is an image obtained by loading the backscattered electron image of FIG. 10 into image processing software. [Figure 12] FIG. 12 is a diagram for explaining a concentration cross section graph. [Figure 13] FIG. 13 is a diagram for explaining a method for defining the black region and the bonding phase. [Figure 14] FIG. 14 is a diagram for explaining the boundary between the black region and the binder phase. [Figure 15] FIG. 15 is an image obtained by binarizing the backscattered electron image of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] [Problem to be solved by this disclosure] Cubic boron nitride (cBN) sintered bodies are used in cutting tools. In this specification, cutting tools including cBN sintered bodies are also referred to as "cBN tools." The cBN sintered body includes cBN particles and a binder phase. The cBN particles form the skeleton of the cBN sintered body. The binder phase includes a ceramic material. The ceramic material includes, for example, titanium nitride (TiN) and the like.

[0007] cBN tools are used in cutting hardened steel. Hardened steel is used, for example, in automotive parts (gears, shafts, and bearings). When cutting hardened steel, the life of cBN tools tends to be unstable. When cutting hardened steel, especially high-strength hardened steel, the life of cBN tools tends to be particularly short.

[0008] High-strength hardened steel is formed by dispersing hard particles inside the hardened steel. In cutting high-strength hardened steel, the surface of the cBN tool is scraped by the hard particles contained in the high-strength hardened steel. This can cause the cBN particles to fall off. The cBN particles form the skeleton of the cBN sintered body. When a part of the skeleton falls off, sudden chipping can occur in the cBN sintered body. In addition, when a part of the skeleton falls off, wear on the flank can progress rapidly. As a result, the cutting resistance can increase rapidly and chipping can occur. Conventionally, in terms of the life of the cBN tool, in cutting high-strength hardened steel, the cBN tool is often used at a cutting speed of, for example, 150 m / min or less.

[0009] An object of the present disclosure is to improve the life of cBN tools.

[0010] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure are listed. Here, an overview of the embodiments of the present disclosure is described.

[0011] (1) Cubic boron nitride sintered bodies contain cubic boron nitride particles, a binder phase, and an intervening phase. Cubic boron nitride particles account for 20% to 80% by volume of the cubic boron nitride sintered body. The total volume ratio of the binder phase and the intervening phase is calculated by subtracting the volume ratio of the cubic boron nitride particles from the volume ratio of the cubic boron nitride sintered body, which is 100% by volume. The binder phase comprises one or more components selected from the group consisting of compounds and solid solutions. Each of the compound and the solid solution includes a first element and a second element. The first element is at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen. The second element is at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, and aluminum in the periodic table. The intervening phase is interposed between the cubic boron nitride particles and the binder phase. The intervening phase contains aluminum, nitrogen, boron, and oxygen. The sum of the average atomic concentration of aluminum contained in the intervening phase and the average atomic concentration of nitrogen contained in the intervening phase is 50.0 atomic % or more. The ratio of the average atomic concentration of nitrogen contained in the intervening phase to the average atomic concentration of boron contained in the intervening phase exceeds 1.00.

[0012] It is believed that during cutting of high-strength hardened steel, cracks are generated inside the cBN sintered body, and these cracks propagate, causing chipping.

[0013] According to the new findings of the present disclosure, cracks selectively pass through the interface between the cBN particles and the binder phase. Brittle materials are scattered at the interface between the cBN particles and the binder phase. It is believed that the brittle materials can be the initiation points or propagation paths of cracks. The brittle materials can be, for example, TiB2, AlB2, Al2O3, etc. It is believed that the brittle materials originate from the cBN particles and the binder (precursor of the binder phase).

[0014] In the cBN sintered body of the present disclosure, instead of the brittle material, an interstitial phase is present between the cBN particles and the binder phase. The interstitial phase has a specific composition. That is, the interstitial phase contains aluminum (Al), nitrogen (N), boron (B) and oxygen (O).

[0015] The main components of the interstitial phase are Al and N. That is, the sum of the average atomic concentration of Al contained in the interstitial phase and the average atomic concentration of N contained in the interstitial phase is 50.0 atomic % or more. Hereinafter, in this specification, this sum is referred to as the "total concentration (Al+N) " is also written.

[0016] The interstitial phase can have metallic ductility because the main components of the interstitial phase are Al and N. The interstitial phase can absorb external stress due to metallic ductility. It is believed that the initiation and propagation of cracks are suppressed by the interstitial phase absorbing stress.

[0017] Furthermore, the ratio of the average atomic concentration of N contained in the interstitial phase to the average atomic concentration of B contained in the interstitial phase exceeds 1.00. Hereinafter, this ratio is referred to as "concentration ratio (N / B) " In the intervening phase, the atomic concentration of N is higher than the atomic concentration of B, which can improve the adhesion between the cBN particles and the binder phase. This can prevent the cBN particles from falling off.

[0018] The interstitial phase's effect of absorbing stress and its effect of improving adhesion work synergistically to improve the chipping resistance of the cBN sintered body, thereby improving the life of cBN tools.

[0019] (2) The intervening phase may further contain carbon. When a line analysis of atomic concentration is performed in the thickness direction of the intervening phase, the atomic concentration of aluminum has a single maximum value. The ratio of the average atomic concentration of carbon to the average atomic concentration of aluminum may be 0.01 or more and 0.30 or less.

[0020] Hereinafter, in this specification, the ratio of the average atomic concentration of carbon (C) to the average atomic concentration of Al is referred to as the "concentration ratio (C / Al) " is also written.

[0021] The interstitial phase of the present disclosure contains components derived from the binder. Among the components derived from the binder, metal elements other than Al (e.g., Ti, W, etc.) tend to have low adhesion to the cBN particles. Therefore, among the components derived from the binder, metal elements other than Al may diffuse into the interstitial phase, thereby decreasing the adhesion between the cBN particles and the binder phase.

[0022] By containing a specific amount of carbon relative to Al in the interstitial phase, it is possible to suppress the diffusion of metal elements other than Al into the interstitial phase, which can improve the adhesion between the cBN particles and the binder phase.

[0023] (3) The cubic boron nitride particles may account for 35 volume % or more and less than 75 volume % of the cubic boron nitride sintered body.

[0024] The higher the volume ratio of cBN particles, the more the chipping resistance tends to improve. On the other hand, the higher the volume ratio of cBN particles, the more the wear resistance tends to decrease. By making the volume ratio of cBN particles 35 volume% or more and less than 75 volume%, the probability of contact between cBN particles inside the cBN sintered body can be moderate. As a result, the chipping resistance and wear resistance of the cBN sintered body can be improved.

[0025] (4) The binder phase may contain titanium and may further contain one or more selected from the group consisting of zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten.

[0026] The strength and toughness of the binder phase can be improved by including titanium (Ti) and niobium (Nb) in the binder phase. This is believed to be because solid solution strengthening occurs due to Nb. The high strength and toughness of the binder phase can improve the wear resistance and chipping resistance of the cBN sintered body.

[0027] (5) The average thickness of the intervening phase may be 5 nm or more and 100 nm or less.

[0028] By setting the average thickness of the intervening phase to be 5 nm or more and 100 nm or less, the life of the cBN tool can be improved.

[0029] (6) The average thickness of the intervening phase may be 5 nm or more and 20 nm or less.

[0030] When the average thickness of the intervening phase is 5 nm or more and 20 nm or less, the life of the cBN tool can be further improved.

[0031] (7) Oxygen may be present as a solid solution in the components contained in the binder phase.

[0032] An oxide layer is formed on the surface of the cBN particles. The oxide layer is several nm thick. It is thought to contain B2O3 and the like. Traditionally, nitrides such as TiN and TiCN have been used as binders. It is thought that during sintering, the oxide layer (B2O3) reacts with the binder (TiN, TiCN, etc.) to produce brittle substances (TiB2, etc.) at the interface between the cBN particles and the binder.

[0033] In the new process disclosed herein, for example, the above-mentioned interstitial phase is formed instead of the brittle material. In one of the new processes disclosed herein, an oxide may be used as a raw material for the binder. It is believed that the use of an oxide as a raw material for the binder (precursor of the binder phase) results in a trace amount of oxygen being dissolved in the binder phase of the final product.

[0034] In the past, for example, when the raw powder of the cBN sintered body was pulverized, the surface of the particles was oxidized, and oxygen was introduced into the cBN sintered body. However, the oxygen introduced in this way could have a negative effect on the sinterability and bonding strength. On the other hand, with the new process disclosed here, the oxygen dissolved in the bonding phase is expected to strengthen the bonding phase.

[0035] (8) The cutting tool of the present disclosure includes the cubic boron nitride sintered body described in any one of (1) to (7) above. The cutting tool of the present disclosure, that is, the cBN tool, can have a long life, for example, in the machining of high-strength hardened steel.

[0036] (9) The cutting tool described in (8) above may be a coated cutting tool. The coated cutting tool includes a coating film. The coating film covers at least a part of the surface of the cubic boron nitride sintered body.

[0037] [Effects of the Present Disclosure] According to the present disclosure, the life of the cBN tool can be improved.

[0038] [Details of Embodiments of the Present Disclosure] Hereinafter, details of embodiments of the present disclosure (referred to as "the present embodiments" in this specification) will be described. However, the following description does not limit the scope of the claims.

[0039] [cBN Sintered Body] FIG. 1 is an example of a cross-sectional image of the cBN sintered body in the present embodiment. The cubic boron nitride (cBN) sintered body includes cubic boron nitride (cBN) particles 11, a bonding phase 12, and an intervening phase 13. The intervening phase 13 is interposed between the cBN particles 11 and the bonding phase 12. The cBN sintered body may substantially consist only of the cBN particles 11, the bonding phase 12, and the intervening phase 13.

[0040] [Intervening Phase] The cross-sectional image in FIG. 1 is a HAADF-STEM (high-angle annular dark field scanning transmission electron microscope) image. FIG. 1 shows the interface between the cBN particles 11 and the bonding phase 12. In the present embodiment, the intervening phase 13 is specified by the following procedure.

[0041] For example, a cross-sectional sample is taken from a cBN sintered body using a FIB (focused ion beam) device. The cross-sectional sample is observed using a STEM. The observation magnification is, for example, about 500,000 times. HAADF images are taken at five randomly selected locations. Furthermore, elemental mapping is performed at each of the five locations using an EDX (energy dispersive x-ray spectroscopy) attached to the STEM. Note that five locations are photographed here, but five locations is merely an example. The number of locations photographed can be set to a sufficient number so that average structural information can be obtained. If the number of locations photographed is too small, there is a possibility that average structural information cannot be obtained if a unique location is included in the randomly selected locations.

[0042] FIG. 2 shows the mapping result of Al in the image of FIG. Al is uniformly distributed at the interface between the cBN particles 11 and the binder phase 12 .

[0043] Furthermore, EDX line analysis is performed in a direction substantially perpendicular to the direction in which the interface between the cBN particles 11 and the binder phase 12 extends. That is, a multi-element simultaneous analysis is performed on a straight line (AB) connecting points A and B in FIG. 1. The length of the straight line is 0.1004 μm. On the straight line (AB), the distance between adjacent measurement points is 0.0024 μm. The number of measurement points is 43. The direction substantially perpendicular to the direction in which the interface between the cBN particles 11 and the binder phase 12 extends corresponds to the thickness direction of the intervening phase 13.

[0044] FIG. 3 is a graph showing the results of the line analysis. The intervening phase 13 of this embodiment is considered to be composed of a non-stoichiometric compound. The intervening phase 13 contains Al, N, B, and O. The intervening phase 13 may be composed substantially only of Al, N, B, and O. The intervening phase 13 may further contain, for example, C, etc.

[0045] FIG. 4 is a graph showing the atomic concentration distribution of Al in FIG. FIG. 5 is a graph showing the atomic concentration distribution of N in FIG. FIG. 6 is a graph showing the atomic concentration distribution of B in FIG. FIG. 7 is a graph showing the atomic concentration distribution of O in FIG. FIG. 8 is a graph showing the atomic concentration distribution of C in FIG.

[0046] (Identification of intervening phase) As shown in FIG. 4, the atomic concentration of Al has a single maximum value in the line analysis. On both sides of the position where the atomic concentration of Al shows a maximum value, two positions are identified where the atomic concentration of Al is half the maximum value. Of the two positions, the position closer to point A is defined as the interface between the cBN particle 11 and the intervening phase 13. Hereinafter, the interface between the cBN particle 11 and the intervening phase 13 is also referred to as the "first interface." Of the two positions, the position closer to point B is defined as the interface between the intervening phase 13 and the binder phase 12. Hereinafter, the interface between the intervening phase 13 and the binder phase 12 is also referred to as the "second interface."

[0047] The region from the first interface to the second interface is the interstitial phase 13. Measurement points contained in the interstitial phase 13 are identified. In the examples of Figures 1 to 8, the thickness of the interstitial phase 13 is 9.6 nm. Five measurement points are contained in the interstitial phase 13. The number of measurement points contained in the interstitial phase 13 varies depending on the thickness of the interstitial phase 13.

[0048] The atomic concentrations of Al at the five measurement points included in the intervening phase 13 are averaged. This gives the average value of the atomic concentration of Al. Similarly, the average values ​​of the atomic concentrations of N, B, and C are obtained. In this specification, the "average value" refers to the arithmetic mean unless otherwise specified.

[0049] (Total concentration (Al+N) ) In the intervening phase 13 of the present embodiment, the sum of the average atomic concentration of Al and the average atomic concentration of N (i.e., the “total concentration (Al+N)") is 50.0 atomic % or more. That is, the main components of the interstitial phase 13 are Al and N. Therefore, it is considered that the interstitial phase 13 can absorb external stress.

[0050] In this embodiment, the total concentration (Al+N) is valid up to the first decimal place. The second decimal place and after are rounded off. Total concentration (Al+N) The total concentration may be, for example, 50.0 atomic % or more and 75.2 atomic % or less. (Al+N) may be, for example, 60.5 atomic % or more and 65.0 atomic % or less.

[0051] (concentration ratio (N / B) ) In the intervening phase 13 of the present embodiment, the ratio of the average atomic concentration of N to the average atomic concentration of B (i.e., the “concentration ratio”) (N / B) " ) exceeds 1.00. This can improve the adhesion between the cBN particles 11 and the binder phase 12.

[0052] In this embodiment, the concentration ratio (N / B) is valid up to two decimal places. Anything after the third decimal place is rounded off. Concentration ratio (N / B) The concentration ratio may be, for example, 1.21 or more and 3.90 or less. (N / B) The concentration ratio may be, for example, 1.70 or more and 3.10 or less. (N / B) may be, for example, 2.00 or more and 2.50 or less.

[0053] (concentration ratio (C / Al) ) In the intervening phase 13 of the present embodiment, the ratio of the average atomic concentration of C to the average atomic concentration of Al (i.e., the “concentration ratio”) (C / Al) ") may be, for example, 0.01 or more and 0.30 or less. This can suppress the diffusion of metal elements other than Al (for example, Ti, etc.) from the binder phase 12 to the intervening phase 13.

[0054] In this embodiment, the concentration ratio (C / Al) is valid up to two decimal places. Anything after the third decimal place is rounded off. Concentration ratio (C / Al)The concentration ratio may be, for example, 0.03 or more and 0.28 or less. (C / Al) The concentration ratio may be, for example, 0.03 or more and 0.26 or less. (C / Al) The concentration ratio may be, for example, 0.03 or more and 0.18 or less. (C / Al) may be, for example, 0.18 or more and 0.30 or less.

[0055] (average thickness) The thickness of the intervening phase 13 is the distance between the first interface and the second interface on the line (AB). The thickness is measured, for example, at five points. The average of the thicknesses at the five points is the "average thickness value." For the average thickness value, only the integer part is valid. The value is rounded off to the nearest whole number.

[0056] The average thickness may be, for example, 4 nm or more and 120 nm or less. The average thickness may be, for example, 5 nm or more and 100 nm or less. When the average thickness of the intervening phase 13 is 5 nm or more and 100 nm or less, the life of the cBN tool may be improved. The average thickness may be, for example, 5 nm or more and 50 nm or less. The average thickness may be, for example, 5 nm or more and 20 nm or less. When the average thickness of the intervening phase 13 is 5 nm or more and 20 nm or less, the life of the cBN tool may be further improved. The average thickness may be, for example, 7 nm or more and 11 nm or less. The average thickness may be, for example, 11 nm or more and 20 nm or less.

[0057] 《Binding phase》 The binder phase 12 bonds the cBN particles 11 together. In the cBN sintered body, the binder phase 12, together with the interstitial phase 13, occupies the remainder of the cBN particles 11. That is, the total of the binder phase 12 and the interstitial phase 13 occupies the remainder of the cBN particles 11 in the cBN sintered body. The total volume ratio of the binder phase 12 and the interstitial phase 13 is a value obtained by subtracting the volume ratio of the cBN particles 11 from 100 volume % when the volume ratio of the cBN sintered body is 100 volume %. The total of the binder phase 12 and the interstitial phase 13 may occupy, for example, 20 volume % or more and 80 volume % or less of the cBN sintered body.

[0058] The binder phase 12 includes one or more components. The binder phase 12 may consist essentially of one component. The binder phase 12 may consist of two or more components. The components included in the binder phase 12 include one or more components selected from the group consisting of a compound and a solid solution. That is, the binder phase 12 includes one or more components selected from the group consisting of a compound and a solid solution. The binder phase 12 may consist essentially of a compound. The binder phase 12 may consist essentially of a solid solution. The binder phase 12 may include both a compound and a solid solution. The composition of the binder phase 12 can be identified by, for example, XRD (x-ray diffraction) and EDX.

[0059] The compound and the solid solution contained in the binder phase 12 each contain a first element and a second element. The compound and the solid solution each independently contain a first element and a second element. The combination of the first element and the second element contained in the compound and the combination of the first element and the second element contained in the solid solution may be the same or different. The first element is a nonmetallic element. The first element is one or more elements selected from the group consisting of nitrogen (N), carbon (C), boron (B) and oxygen (O). That is, the compound and the solid solution may be a nitride, a carbide, a boride, or an oxide. The compound and the solid solution may be, for example, a carbide and a nitride. That is, the compound and the solid solution may be, for example, a carbonitride or the like.

[0060] The second element is a metal element. The second element is one or more selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, and Al in the periodic table. The Group 4 element may be, for example, one or more selected from the group consisting of titanium (Ti), zirconium (Zr), and hafnium (Hf). The Group 5 element may be, for example, one or more selected from the group consisting of vanadium (V), niobium (Nb), and tantalum (Ta). The Group 6 element may be, for example, one or more selected from the group consisting of chromium (Cr), molybdenum (Mo), and tungsten (W).

[0061] The binder phase 12 may contain Ti. In addition to Ti, the binder phase 12 may further contain one or more selected from the group consisting of Zr, Nb, Mo, Hf, Ta and W. This can improve the strength and toughness of the binder phase.

[0062] The binder phase may include, for example, one or more selected from the group consisting of TiCN, TiNbN, TiB2, Al compounds (e.g., Al2O3, AlN, etc.), TiNbCN, TiZrCN, TiMoCN, TiNbZrCN, TiHfCN, TiTaCN, and TiWCN.

[0063] In addition, the composition formula in this specification should not be limited to only the atomic ratio shown in the formula. The composition formula should be understood to include all conventionally known atomic ratios. The composition formula should be understood to include, for example, non-stoichiometric ratios. For example, the atomic ratio of Ti, C, and N in "TiCN" is not limited to only "Ti:C:N=1:0.5:0.5". In addition, the composition formula in this specification shows not only the composition of a compound, but also the composition of a solid solution. The solid solution may be an interstitial solid solution or a substitutional solid solution.

[0064] The components contained in the binder phase 12 may contain oxygen (O) in a solid solution. The dissolved oxygen may be oxygen derived from the raw material of the binder (the precursor of the binder phase 12). The dissolved oxygen may improve the strength and toughness of the binder phase 12. The dissolved oxygen may be detected, for example, by EDX attached to the STEM. The dissolved oxygen may occupy, for example, 1.0 atomic % or more and 5.0 atomic % or less of the binder phase 12.

[0065] 《cBN particles》 The cBN particles 11 form the skeleton of the cBN sintered body. The cBN particles 11 contain cBN. The cBN particles 11 may contain, for example, a small amount of impurities. The cBN particles 11 may contain, for example, a small amount of wurtzite boron nitride (wBN). The cBN particles 11 may be substantially composed of cBN only.

[0066] The cBN particles 11 occupy 20% by volume or more and 80% by volume or less of the cBN sintered body. Only the integer part of the volume ratio of the cBN particles 11 is valid. The decimal point is rounded off. The method of measuring the volume ratio will be described later. If the volume ratio of the cBN particles 11 is less than 20% by volume, the cBN tool cannot be expected to have a sufficient life. Since the cBN particles 11 play the role of the skeleton of the cBN sintered body, it is considered that the chipping resistance decreases when the contact probability between the cBN particles 11 is excessively low. If the volume ratio of the cBN particles 11 exceeds 80% by volume, the cBN tool cannot be expected to have a sufficient life. It is considered that the contact probability between the cBN particles 11 becomes excessively high, and the intervening phase 13 interposed between the cBN particles 11 and the binder phase 12 relatively decreases. The volume ratio of the cBN particles 11 may be, for example, 35% by volume or more and less than 75% by volume. Within this range, the probability of contact between the cBN particles 11 can be moderate. As a result, the effect of the intervening phase 13 interposed between the cBN particles 11 and the binder phase 12 becomes greater, and the chipping resistance and wear resistance of the cBN sintered body can be improved. The volume ratio of the cBN particles 11 may be, for example, 45 volume % or more and 70 volume % or less. The volume ratio of the cBN particles 11 may be, for example, 45 volume % or more and 60 volume % or less.

[0067] The cBN particles 11 may have an average particle size of, for example, 0.1 μm or more and 10 μm or less. The cBN particles 11 may have an average particle size of, for example, 1 μm or more and 5 μm or less. The "particle size of the cBN particles 11" indicates the circle equivalent diameter of the cBN particles 11 in a cross-sectional image of the cBN sintered body. The "average particle size of the cBN particles 11" is, for example, the arithmetic average of the particle sizes of 10 or more cBN particles 11. The 10 or more cBN particles 11 are randomly extracted from the cross-sectional image of the cBN sintered body.

[0068] (Volume ratio measurement method) The volume ratio of cBN particles can be measured by a scanning electron microscope (SEM). For example, a JSM-7800F manufactured by JEOL Ltd. may be used. An apparatus having the same function as the above apparatus may also be used.

[0069] The method for measuring the volume ratio of cBN particles is as follows. The cBN sintered body is cut at a desired position. The cut surface is processed, for example, with a CP (cross section polisher), thereby preparing a cross-sectional sample. The cross-sectional sample is observed in the backscattered electron mode of the SEM, thereby obtaining a backscattered electron image. The observation magnification can be, for example, about 5000 times. In the backscattered electron image, the areas where the cBN particles exist are black, and the areas where the binder phase exists are gray or white.

[0070] Next, the backscattered electron image is binarized using image analysis software (WinROOF, manufactured by Mitani Shoji Co., Ltd.). From the binarized image, the area ratio of pixels originating from the dark field (pixels originating from cBN particles) to the area of ​​the measurement field is calculated. The calculated area ratio is regarded as the volume ratio of cBN particles.

[0071] For example, the volume ratio of the binding phase may be calculated by calculating the area ratio of pixels originating from the bright field (pixels originating from the binding phase) to the area of ​​the measurement field from the image after binarization processing.

[0072] A specific method of the binarization process will be described with reference to FIGS. Fig. 10 is an example of a backscattered electron image of a cBN sintered body. The backscattered electron image is loaded into image processing software. The loaded image is shown in Fig. 11. As shown in Fig. 11, an arbitrary line Q1 is set in the loaded image.

[0073] The concentration is measured along the line Q1, and the GRAY value is read. A graph (hereinafter also referred to as a "concentration cross-sectional graph") is created with the line Q1 as the X-coordinate and the GRAY value as the Y-coordinate. A backscattered electron image of a cBN sintered body and a concentration cross-sectional graph of the backscattered electron image are shown in FIG. 12. In FIG. 12, the upper image is the backscattered electron image, and the lower graph is the concentration cross-sectional graph. In FIG. 12, the width of the backscattered electron image and the width of the X-coordinate of the concentration cross-sectional graph (23.27 μm) are the same. Therefore, the distance from the left end of the line Q1 in the backscattered electron image to a specific position on the line Q1 is indicated by the value of the X-coordinate of the concentration cross-sectional graph.

[0074] Three black regions in which cBN particles exist are arbitrarily selected in the backscattered electron image of Fig. 12. The black regions are, for example, the portions indicated by the ellipses marked with the symbol c in the backscattered electron image of Fig. 13.

[0075] The gray values ​​of the three black regions are read from the density cross section graph. The gray values ​​of the three black regions are taken as the average value of the gray values ​​in the three portions surrounded by the ellipse marked c in the density cross section graph of FIG. 13. The average value of the gray values ​​in the three portions is calculated. This average value is the gray value of cBN (hereinafter referred to as "G cbn " It is also written as ".

[0076] Three regions in which the bond phase exists, which are shown in gray in the backscattered electron image of Fig. 12, are arbitrarily selected. The bond phase is, for example, the portion shown by the ellipse indicated by the symbol d in the backscattered electron image of Fig. 13.

[0077] The GRAY values ​​of the three binding phases are read from the concentration cross-sectional graph. The GRAY values ​​of the three binding phases are the average values ​​of the GRAY values ​​in the three areas surrounded by the ellipses denoted by d in the concentration cross-sectional graph of FIG. 13. The average value of the GRAY values ​​in the three areas is calculated. This average value is the GRAY value of the binding phase (hereinafter, "GRAY value"). binder " It is also written as ".

[0078] (G cbn +G binder The gray value indicated by the formula (1) / 2 is defined as the gray value of the interface between the black region (cBN particle) and the binder phase. For example, in the concentration cross-sectional graph of FIG. 13, the gray value G cbn Line G cbn The GRAY value of the bonded phase is G binder Line G binder (G cbn +G binder The GRAY value represented by (G1) / 2 is shown by line G1.

[0079] As described above, by defining the interface between the black region (cBN particles) and the binder phase in the concentration cross section graph, the values ​​of the X and Y coordinates at the interface between the black region (cBN particles) and the binder phase are read. In the backscattered electron image of FIG. 14, the interface between the black region (cBN particles) and the binder phase is the portion indicated by the ellipse with the symbol e. In the concentration cross section graph of FIG. 14, the interface between the black region (cBN particles) and the binder phase is the portion indicated by the arrow e. The values ​​of the X and Y coordinates at the arrow e correspond to the values ​​of the X and Y coordinates at the interface between the black region (cBN particles) and the binder phase. The interface can be set arbitrarily. In the example of FIG. 14, the portion including the interface is indicated as the ellipse e.

[0080] The binarization process is performed by setting the X-coordinate and Y-coordinate values ​​at the interface between the black region (cBN particle) and the bonding phase as threshold values. The image after the binarization process is shown in FIG. 15. In FIG. 15, the area surrounded by the dotted line is the area to which the binarization process has been applied. Note that the image after the binarization process may contain a white area in addition to the bright field (gray area) and the dark field (black area). The white area is an area that was displayed in white in the image before the binarization process.

[0081] In Fig. 15, the area ratio of pixels originating from the dark field (pixels originating from cBN particles) to the area of ​​the measurement field is calculated. The calculated area ratio is regarded as the volume ratio of cBN particles.

[0082] For example, in FIG. 15, the volume ratio of the bonding phase may be calculated by calculating the area ratio of the pixels (pixels derived from the bonding phase) derived from the bright field in the area of the measurement field of view.

[0083] <Method for manufacturing cBN sintered body> The cBN sintered body of the present embodiment can be manufactured, for example, by the following manufacturing method. FIG. 9 is a flowchart showing the manufacturing method of the cBN sintered body in the present embodiment. The manufacturing method of the cBN sintered body of the present embodiment includes “(A) Preparation of binder”, “(B) Preparation of raw material powder” and “(C) Sintering”.

[0084] In the present embodiment, a binder having a specific composition may be used so that an intervening phase is formed. The surface of the cBN particles may be modified so that an intervening phase is formed. A binder having a specific composition may be used and the surface of the cBN particles may be modified.

[0085] 《(A) Preparation of binder》 In the present embodiment, a binder is prepared by mixing a first material and a second material. The binder is a precursor of the bonding phase. The mixing ratio of the first material and the second material can be appropriately changed according to the composition of the target bonding phase. The mixing ratio of the first material and the second material may be, for example, “first material: second material = 1: 3 to 3: 1 (mass ratio)”.

[0086] (First material) The first material is a material that becomes the main component of the bonding phase. The first material is also referred to as the “main binder”. The first material may contain, for example, one or more selected from the group consisting of TiC, TiN, and TiCN.

[0087] It is desirable that mutual diffusion of elements hardly occurs between the first material and the second material described later. This is because when mutual diffusion of elements hardly occurs, the reaction between the second material and the cBN particles is promoted, and the formation of the intervening phase is promoted.

[0088] The first material may have a composition represented by, for example, formula (I): TiMCN, where M in formula (I) is one or more elements selected from the group consisting of Zr, Nb, Mo, Hf, Ta, and W.

[0089] For example, the first material may be prepared by forcibly dissolving M (Nb, etc.) in TiCN, etc. As a result of dissolving M, the crystal structure is thought to be distorted. Therefore, it is thought that interdiffusion of elements between the first material and the second material is unlikely to occur during sintering.

[0090] The first material having the composition of the above formula (I) is prepared, for example, by the following procedure. For example, TiO2 powder, powder of an oxide of M (Nb, etc.), and carbon powder are mixed to prepare a mixed powder. The mixing ratio may be, for example, "TiO2: oxide of M: carbon = 65: 17: 18 (mass ratio)". For example, the mixed powder is heat-treated in a reducing atmosphere. The reducing atmosphere may be, for example, a nitrogen atmosphere. The heat treatment temperature may be, for example, 1800°C or more and 2200°C or less. The heat treatment time may be, for example, about 60 minutes. A single-phase compound having the composition of the above formula (I) can be generated by the heat treatment. Furthermore, the average particle size of the single-phase compound is adjusted, for example, by a wet grinding method.

[0091] The heat treatment temperature during synthesis of a general first material (TiC, TiN, TiCN, etc.) is 1500°C or lower. This temperature is close to the sintering temperature (approximately 1200°C to 1800°C). The above-mentioned first material is heat treated at a temperature of 1800°C or higher and 2200°C or lower. That is, the first material in this embodiment can be heat treated at a temperature equal to or higher than the sintering temperature. By being heat treated in advance at a temperature equal to or higher than the sintering temperature, element diffusion from the first material can be suppressed during actual sintering.

[0092] The first material uses oxides as raw materials, and oxygen contained in the raw materials dissolves in the components of the binder phase, thereby contributing to solution strengthening of the binder phase.

[0093] (Second material) The second material is a component that bonds the first material and the cBN particles. The second material is also called a "secondary binder." Conventionally, for example, intermetallic compounds such as Ti, Al, TiAl, and TiAl3 are used as the second material. In contrast, the second material in this embodiment may include at least one selected from the group consisting of carbides such as Ti2AlC, nitrides such as Ti2AlN, and carbonitrides such as Ti2AlCN.

[0094] It is believed that oxides such as B2O3 are present on the surface of the cBN particles. Carbides such as Ti2AlC, nitrides such as Ti2AlN, and carbonitrides such as Ti2AlCN are expected to promote the decomposition of oxides (such as B2O3) during sintering. Furthermore, oxygen generated by the decomposition of oxides can be reduced by carbon contained in the carbides and carbonitrides. Carbon monoxide (CO) and carbon dioxide (CO2) generated by the reduction reaction are gases and can be easily discharged outside the system. Furthermore, it is expected that the wettability of the cBN particle surface will be improved by the diffusion of carbon to the surface of the cBN particles during the reduction reaction. The improved wettability will result in a thin and uniform distribution of Al on the surface of the cBN particles. As a result, it is expected that the adhesion between the cBN particles and the binder phase will be improved.

[0095] In addition, carbon can inhibit the diffusion of metal elements other than Al into the interstitial phase, which is expected to improve the adhesion between the cBN particles and the binder phase.

[0096] Ti2AlC is prepared, for example, by the following procedure. For example, Ti powder, Al powder, and TiC powder are mixed to prepare a mixed powder. The mixing ratio may be, for example, "Ti:Al:TiC=37:22:41 (mass ratio)". For example, the mixed powder is heat-treated in a vacuum atmosphere. The heat treatment temperature may be, for example, about 1500°C. The heat treatment time may be, for example, about 30 minutes. By the heat treatment, for example, a single-phase compound of Ti2AlC may be generated. Furthermore, the average particle size of the single-phase compound is adjusted, for example, by a wet grinding method.

[0097] (B) Preparation of raw material powder In this embodiment, the raw material powder is prepared by mixing the cBN particles and the binder. For example, the cBN particles and the binder may be mixed by wet mixing. The medium in the wet mixing may be, for example, ethanol. After mixing, the raw material powder may be naturally dried. After mixing, the mixed powder may be subjected to a degassing process. In the degassing process, the raw material powder may be heated to a temperature of 900° C. or higher in a vacuum atmosphere.

[0098] (Surface modification of cBN particles) In this embodiment, the surfaces of the cBN particles may be modified prior to the preparation of the raw material powder. It is expected that the modification of the surfaces of the cBN particles will promote the formation of the interstitial phase.

[0099] An oxide layer is formed on the surface of the cBN particle. The oxide layer may be, for example, crystalline or amorphous. The oxide layer may have a composition such as B2O3. It is believed that the oxide layer is formed by the adsorption of moisture and oxygen to the surface of the cBN particle during cleaning and exposure to the air. The oxide layer has a variation in thickness. It is believed that the variation in the thickness of the oxide layer affects the diffusion of B and N during sintering. As a result, it is believed that a brittle material is generated.

[0100] For example, the surface of the cBN particles may be modified so that the thickness of the oxide layer is uniform, or the surface of the cBN particles may be modified so that an organic material is attached to the surface of the cBN particles.

[0101] For example, the cBN particles may come into contact with an organic material in supercritical water. The organic material may be, for example, hexylamine and paraffin. In supercritical water, it is expected that a thick portion of the oxide layer will be selectively dissolved, and the thickness of the oxide layer will become uniform. Furthermore, it is expected that carbon having a reducing effect will be introduced to the surface of the cBN particles by modifying the surface of the cBN particles with an organic material. In addition, the surface of the cBN particles may be modified by, for example, irradiating the surface of the cBN particles with plasma.

[0102] (C) Sintering In this embodiment, the raw material powder is sintered to produce a cBN sintered body.

[0103] For example, the raw powder after degassing is filled into a capsule. If the raw powder is left in the air after the degassing, moisture and oxygen in the air may be adsorbed by the raw powder. Therefore, it is desirable to fill the capsule with the raw powder promptly after the degassing.

[0104] The capsule may be made of, for example, Ta. The capsule is sealed with a metal sealant. For example, a belt-type ultra-high pressure, high temperature generator is used for the sintering operation. The sealed capsule is set in the belt-type ultra-high pressure, high temperature generator. The raw material powder is sintered by the belt-type ultra-high pressure, high temperature generator. The pressure during sintering may be, for example, 5.5 GPa or more and 8 GPa or less. The temperature during sintering may be, for example, 1200°C or more and less than 1800°C. When the pressure during sintering is 6 GPa or more and 7 GPa or less and the temperature during sintering is 1400°C or more and 1600°C or less, for example, a good balance between manufacturing cost and performance is achieved.

[0105] In addition, if the surface of the cBN particles is modified with an organic material, the organic material will decompose when heated during sintering. It is believed that the gas generated by the decomposition of the organic material will uniformly permeate the gaps in the green compact (raw powder). It is possible that some of the decomposed organic material will remain on the surface of the cBN particles.

[0106] <Cutting tool> The cutting tool of this embodiment includes the cBN sintered body of this embodiment. In the cutting tool, the cBN sintered body functions as a cutting edge. The cutting tool may consist essentially of only the cBN sintered body. The cutting tool may further include components other than the cBN sintered body. For example, the cutting tool may include a carbide alloy base alloy. The cBN sintered body may be installed at the cutting edge of the base alloy.

[0107] The cutting tool of this embodiment may be a coated cutting tool. The coated cutting tool includes a coating film. The coating film covers at least a part of the surface of the cBN sintered body. The coating film includes, for example, a ceramic material or the like.

[0108] The shape of the cBN tool should not be particularly limited. The cBN tool may be, for example, an insert (for drills, end mills, milling, turning, etc.), a metal saw, a toothing tool, a reamer, a tap, or a bit.

Examples

[0109] Examples of the present disclosure (also referred to as "this example" in this specification) are described below. However, the following description does not limit the scope of the claims.

[0110] <Manufacture of cBN sintered body> Samples 1 to 22 shown in Table 1 below were manufactured. Samples 1 to 19 are examples. Samples 20 to 22 are comparative examples.

[0111] 《Sample 1》 As the first material, TiCN was prepared. TiCN had an average particle size of 0.5 μm.

[0112] A mixed powder was prepared by mixing Ti powder, Al powder, and TiC powder. The mixing ratio was "Ti:Al:TiC = 37:22:41 (mass ratio)". The mixed powder was heat-treated. The heat treatment conditions are as follows.

[0113] Heat treatment conditions Atmosphere Vacuum Temperature 1520℃ Duration 30 mins

[0114] A single-phase compound was formed by the heat treatment. The single-phase compound was believed to have a composition of approximately Ti2AlC. The single-phase compound was then pulverized by ball milling to prepare the second material. The second material had an average particle size of 0.5 μm.

[0115] The binder was prepared by mixing the first material and the second material in a mixing ratio of "first material:second material=1:3 (mass ratio)".

[0116] cBN particles were prepared. The cBN particles had an average particle size of 3 μm. The cBN particles and a binder were mixed using a ball mill. In this way, a raw material powder was prepared. The mixing ratio was "cBN particles: binder = 70:30 (volume ratio)".

[0117] The raw material powder was filled into a capsule. The capsule was made of Ta. The capsule was sealed with a metal sealant. The sealed capsule was set in a belt-type ultra-high pressure and high temperature generator. The raw material powder was sintered in the belt-type ultra-high pressure and high temperature generator. The sintering conditions were as follows. As a result of the above, a cBN sintered body relating to sample 1 was produced.

[0118] Sintering conditions Pressure: 6.5GPa Temperature 1500℃ Duration 15 min

[0119] Sample 2 A supercritical water nanoparticle synthesis test machine (product name "MOMI super mini", manufactured by ITEC Co., Ltd.) was prepared. Supercritical water was generated using this test machine. The conditions for generating supercritical water were as follows:

[0120] Conditions for generating supercritical water Pressure 34MPa Temperature 381℃ Flow rate 2ml / min

[0121] Hexylamine was prepared as an organic material. cBN particles were prepared. The cBN particles had an average particle size of 3 μm.

[0122] In this test machine, hexylamine and cBN particles were continuously added to supercritical water. In the mixture of supercritical water, hexylamine, and cBN particles, the hexylamine content was 10 mass%. In the same mixture, the cBN particle content was 10 mass%. This reduced the oxide layer (B2O3) on the surface of the cBN particles. In addition, carbon derived from organic materials was modified on the surface of the cBN particles. It is believed that the carbon forms a very thin, uniform film on the surface of the cBN particles.

[0123] The organic substance (modifying material) modifying the surface of the cBN particles was identified by GC-MS (gas chromatography - mass spectrometry), and the amount of the modifying material was quantified at the same time. The amount of carbon modification was calculated from the molecular formula of the modifying material and the amount of modification by the modifying material. The amount of carbon modification was 529 ppm. In this way, modified cBN particles were prepared.

[0124] A cBN sintered body according to Sample 2 was produced by carrying out the same operation as Sample 1, except that the modified cBN particles obtained above were used instead of cBN particles.

[0125] Sample 3 A cBN sintered body according to Sample 3 was produced by carrying out the same operation as Sample 2, except that the content of hexylamine in the mixture consisting of supercritical water, hexylamine and cBN particles was changed to 1 mass %. In Sample 3, the amount of carbon modification was 48 ppm.

[0126] Sample 4 The cBN sintered body of Sample 4 was produced by carrying out the same operations as those for Sample 2, except that the mixing ratio of the modified cBN particles and the binder was changed to "modified cBN particles:binder = 60:40 (volume ratio)".

[0127] Sample 5 The cBN sintered body of Sample 5 was produced by carrying out the same operations as those for Sample 2, except that the mixing ratio of the modified cBN particles and the binder was changed to "modified cBN particles:binder = 45:55 (volume ratio)".

[0128] Sample 6 The cBN sintered body of Sample 6 was produced by carrying out the same operations as those for Sample 2, except that the mixing ratio of the modified cBN particles and the binder was changed to "modified cBN particles:binder = 20:80 (volume ratio)".

[0129] Sample 7 The cBN sintered body of Sample 7 was produced by carrying out the same operations as those for Sample 2, except that the mixing ratio of the modified cBN particles and the binder was changed to "modified cBN particles:binder = 80:20 (volume ratio)".

[0130] Sample 8 In the manufacture of sample 8, TiNbCN was used as the first material. The first material was prepared by the following procedure. A mixed powder was prepared by mixing TiO2 powder, Nb2O3 powder, and carbon powder. The mixing ratio was "TiO2:Nb2O3:carbon = 57:17:26 (mass ratio)". The mixed powder was heat treated. The heat treatment conditions were as follows:

[0131] Heat treatment conditions Atmosphere: Nitrogen Temperature 2200℃ Duration 60 mins

[0132] A single-phase compound was formed by the heat treatment. The single-phase compound was pulverized by a ball mill method. This resulted in the preparation of a first material. The first material had an average particle size of 0.5 μm.

[0133] A cBN sintered body according to Sample 8 was manufactured by carrying out the same operation as Sample 4, except that the first material (TiNbCN) obtained above was used.

[0134] Sample 9 A cBN sintered body according to Sample 9 was produced by carrying out the same operation as Sample 8, except that the sintering time was changed to 30 minutes.

[0135] Sample 10 A cBN sintered body according to Sample 10 was manufactured by carrying out the same operation as Sample 8, except that Ti2AlN was used as the second binder. The Ti2AlN in this sample was synthesized by the following procedure. A mixed powder was prepared by mixing Ti powder, Al powder, and TiN powder. The mixing ratio was "Ti:Al:TiN = 31:21:48 (mass ratio)". The mixed powder was heat-treated to synthesize Ti2AlN. The heat treatment conditions were as follows.

[0136] Heat treatment conditions Atmosphere Vacuum Temperature 1550℃ Duration 30 mins

[0137] Sample 11 A cBN sintered body according to Sample 11 was manufactured by carrying out the same operation as Sample 8, except that Ti2AlN was used as the second binder. The Ti2AlN in this sample was synthesized by the following procedure. A mixed powder was prepared by mixing Ti powder, Al powder, and TiN powder. The mixing ratio was "Ti:Al:TiN = 31:22:47 (mass ratio)". The mixed powder was heat-treated to synthesize Ti2AlN. The heat treatment conditions were as follows.

[0138] Heat treatment conditions Atmosphere Vacuum Temperature 1550℃ Duration 30 mins

[0139] Sample 12 A cBN sintered body according to Sample 12 was manufactured by carrying out the same operation as Sample 10, except that TiNbN was used as the first binder. The TiNbN in this sample was synthesized by the following procedure. A mixed powder was prepared by mixing TiN powder (manufactured by Japan New Metals Co., Ltd.) and NbN powder (manufactured by Japan New Metals Co., Ltd.). The mixing ratio was "TiN:NbN = 92:8 (mass ratio)". The mixed powder was heat-treated to synthesize TiNbN. The heat treatment conditions were as follows. After heat treatment, the TiNbN powder was pulverized.

[0140] Heat treatment conditions Atmosphere: Nitrogen Temperature 2200℃ Duration 60 mins

[0141] Sample 13 A cBN sintered body according to Sample 13 was manufactured by carrying out the same operation as Sample 10, except that Ti2AlN synthesized in the following mixture ratio was used. The mixture ratio was "Ti:Al:TiN = 30:25:45 (mass ratio)".

[0142] Sample 14 In the manufacture of sample 14, ZrO2 was used instead of Nb2O3. That is, the mixing ratio of the mixed powder was "TiO2:ZrO2:carbon = 58:16:26 (mass ratio)". Except for the change in the composition of the first material, the same operation as for sample 8 was carried out to manufacture the cBN sintered body of sample 14.

[0143] Sample 15 In the manufacture of sample 15, MoO3 was used instead of Nb2O3. That is, the mixing ratio of the mixed powder was "TiO2:MoO3:carbon = 56:18:26 (mass ratio)". Except for the change in the composition of the first material, the same operation as for sample 8 was carried out to manufacture the cBN sintered body of sample 15.

[0144] Sample 16 In the manufacture of sample 16, Nb2O3 and ZrO2 were used. In other words, the mixing ratio of the mixed powder was "TiO2:Nb2O3:ZrO2:carbon = 57:8.5:8.5:26 (mass ratio)". The cBN sintered body of sample 16 was manufactured by carrying out the same operation as sample 8, except that the composition of the first material was changed.

[0145] Sample 17 In the manufacture of sample 17, HfO2 was used instead of Nb2O3. That is, the mixing ratio of the mixed powder was "TiO2:HfO2:carbon = 53:24:23 (mass ratio)". Except for the change in the composition of the first material, the same operation as for sample 8 was carried out to manufacture the cBN sintered body of sample 17.

[0146] Sample 18 In the manufacture of sample 18, Ta2O5 was used instead of Nb2O3. That is, the mixing ratio of the mixed powder was "TiO2:Ta2O5:carbon = 52:25:23 (mass ratio)". Except for the change in the composition of the first material, the same operation as for sample 8 was carried out to manufacture the cBN sintered body of sample 18.

[0147] Sample 19 In the manufacture of Sample 19, WO3 was used instead of Nb2O3. That is, the mixing ratio of the mixed powder was "TiO2:WO3:carbon = 52:26:22 (mass ratio)". Except for the change in the composition of the first material, the same operation as in Sample 8 was carried out to manufacture the cBN sintered body of Sample 19.

[0148] Sample 20 In the manufacture of Sample 20, the mixing ratio of the modified cBN particles to the binder was "modified cBN particles: binder = 10:90 (volume ratio)." Except for changing the mixing ratio of the modified cBN particles to the binder, the same operation as in Sample 2 was carried out to manufacture the cBN sintered body of Sample 20.

[0149] Sample 21 In the manufacture of Sample 21, the mixing ratio of the modified cBN particles to the binder was "modified cBN particles: binder = 90: 10 (volume ratio)." Except for changing the mixing ratio of the modified cBN particles to the binder, the same operation as in Sample 2 was carried out to manufacture the cBN sintered body of Sample 21.

[0150] Sample 22 A cBN sintered body according to Sample 22 was produced by carrying out the same operation as Sample 1, except that Ti2AlN was used as the second material.

[0151] <Evaluation> The compounds contained in the bond phase were identified by XRD. Furthermore, the composition of the intervening phase was analyzed by STEM-EDX. The results are shown in Table 1 below.

[0152] Each of the cBN sintered bodies produced above was used to manufacture cBN tools. Cutting tests of the cBN tools were carried out under the following conditions:

[0153] Tool Part Number DNGA150412 (Edge treatment S01225)

[0154] Cutting conditions Cutting speed 200m / min Feed speed 0.2mm / rev. Cutting depth 0.15mm Coolant DRY Intermittent cutting

[0155] lathe LB400 Manufactured by Okuma Corporation

[0156] Cutting target Hardened steel SKD11 (high strength hardened steel), hardness 60HRC, V-groove formed on outer circumference.

[0157] In the cutting test, the life of the cBN tool was measured. The results are shown in Table 1 below. The measurement procedure was as follows. The size of chipping was measured at the cutting edge every time 0.1 km of cutting was performed. The size of chipping was defined as the size of the chip in the direction of the principal force. The direction of the principal force is based on the position of the cutting edge ridge before cutting begins. The distance at which the size of chipping at the cutting edge became 0.1 mm or more was considered to be the end of the tool life.

[0158] [Table 1]

[0159] <Result> Samples 1 to 19 contained an interstitial phase. Sample 22 did not contain an interstitial phase. Samples 1 to 19 had a longer life than Sample 22. This is thought to be because the interstitial phase suppressed the initiation and propagation of cracks.

[0160] Sample 20 contained an interstitial phase. However, sample 20 had a short life. This is probably because the volume ratio of cBN particles was less than 20 volume %.

[0161] Sample 21 contained an interstitial phase. However, it had a short life. This is probably because the volume ratio of cBN particles exceeded 80 volume %.

[0162] [Note] A cubic boron nitride sintered body, comprising cubic boron nitride particles, a binder phase and an intercalation phase; the cubic boron nitride particles occupy 20% by volume or more and 80% by volume or less of the cubic boron nitride sintered body, the sum of the binder phase and the intervening phase accounts for the remainder of the cubic boron nitride particles in the cubic boron nitride sintered body, The binder phase comprises one or more components, the component contained in the binder phase includes one or more selected from the group consisting of a compound and a solid solution; each of the compound and the solid solution includes a first element and a second element; the first element is at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen; the second element is at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, and aluminum in the periodic table; the intervening phase is interposed between the cubic boron nitride particles and the binder phase, the interstitial phase comprises aluminum, nitrogen, boron and oxygen; the sum of the average atomic concentration of aluminum contained in the intervening phase and the average atomic concentration of nitrogen contained in the intervening phase is 50.0 atomic % or more; a ratio of the average atomic concentration of nitrogen contained in the interstitial phase to the average atomic concentration of boron contained in the interstitial phase exceeds 1.00; Cubic boron nitride sintered body.

[0163] The present embodiment and examples should be considered to be illustrative in all respects and not restrictive. The scope of the present invention is defined by the claims, not by the present embodiment and examples, and is intended to include the equivalent meaning of the claims and all modifications within the scope. [Explanation of symbols]

[0164] 11 cubic boron nitride (cBN) particles, 12 bound phases, and 13 intervening phases.

Claims

1. A cubic boron nitride sintered body comprising cubic boron nitride particles, a binder phase and an intervening phase, the cubic boron nitride particles occupy 20% by volume or more and 80% by volume or less of the cubic boron nitride sintered body, the total volume ratio of the binder phase and the intervening phase is a value obtained by subtracting the volume ratio of the cubic boron nitride particles from the volume ratio of the cubic boron nitride sintered body, where the volume ratio of the cubic boron nitride sintered body is 100 volume %, the binder phase comprises one or more components selected from the group consisting of compounds and solid solutions; each of the compound and the solid solution includes a first element and a second element; the first element is at least one selected from the group consisting of nitrogen, carbon, boron, and oxygen; the second element is at least one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, and aluminum in the periodic table; the intervening phase is interposed between the cubic boron nitride particles and the binder phase, the interstitial phase comprises aluminum, nitrogen, boron and oxygen; the sum of the average atomic concentration of aluminum contained in the intervening phase and the average atomic concentration of nitrogen contained in the intervening phase is 55.0 atomic % or more; a ratio of an average atomic concentration of nitrogen contained in the interstitial phase to an average atomic concentration of boron contained in the interstitial phase exceeds 1.00; When a line analysis of the atomic concentration was performed in the thickness direction of the intervening phase, The atomic concentration of aluminum has a single maximum, At the interface between the intervening phase and the binder phase, the atomic concentration of aluminum is half of the maximum value. Cubic boron nitride sintered body.

2. The interstitial phase further comprises carbon; a ratio of the average atomic concentration of carbon to the average atomic concentration of aluminum is 0.01 or more and 0.30 or less; 2. The cubic boron nitride sintered body according to claim 1.

3. a ratio of the average atomic concentration of carbon to the average atomic concentration of aluminum is 0.18 or more and 0.30 or less; 3. The cubic boron nitride sintered body according to claim 2.

4. In the intervening phase, the ratio of the average atomic concentration of nitrogen to the average atomic concentration of boron is 1.21 or more.

3. The cubic boron nitride sintered body according to claim 1 or 2.

5. In the intervening phase, a ratio of an average value of the atomic concentration of nitrogen to an average value of the atomic concentration of boron is 1.70 or more and 3.10 or less.

5. The cubic boron nitride sintered body according to claim 4.

6. The intervening phase is composed of aluminum, nitrogen, boron, carbon, and oxygen.

3. The cubic boron nitride sintered body according to claim 1 or 2.

7. the cubic boron nitride particles occupy 35% by volume or more and less than 75% by volume of the cubic boron nitride sintered body; 3. The cubic boron nitride sintered body according to claim 1 or 2.

8. the binder phase comprises titanium; The binder phase further comprises one or more selected from the group consisting of zirconium, niobium, molybdenum, hafnium, tantalum and tungsten; 3. The cubic boron nitride sintered body according to claim 1 or 2.

9. The average thickness of the intervening phase is 5 nm or more and 100 nm or less.

3. The cubic boron nitride sintered body according to claim 1 or 2.

10. The average thickness of the intervening phase is 5 nm or more and 20 nm or less.

3. The cubic boron nitride sintered body according to claim 1 or 2.

11. Oxygen is dissolved in the component contained in the binder phase.

3. The cubic boron nitride sintered body according to claim 1 or 2.

12. The cubic boron nitride sintered body according to claim 1 or 2 is included. cutting tools.

13. the cutting tool is a coated cutting tool; The coated cutting tool includes a coating, The coating covers at least a portion of the surface of the cubic boron nitride sintered body.

13. The cutting tool of claim 12.

Citation Information

Patent Citations

  • Manufacture of cubic boron nitride base sintered body for cutting tool

    JP1986141672A

  • Cubic boron nitride compact

    JP2009513471A

  • Cubic crystal boron nitride sintered cutting tool excellent in defect resistance

    JP2015044259A